THE EFFECT OF SUKUK FINANCING AND CAPITAL STRUCTURE ON FINANCIAL PERFORMANCE AND CORPORATE VALUE: A STUDY OF SUKUK ISSUER LISTED IN INDONESIAN STOCK EXCHANGE (International Journal of Islamic Business, 2019)
This research aims to understand what factors will actually affect the corporate to increased profitability and corporate value, especially for the corporate which issuing syariah bonds or sukuk. In particular, the influence of Sukuk bonds funding integrated with the capital structure to the corporate financial performance and value. This research used panel data that processed by Partial Least Square (PLS) method to see the influence of Sukuk funding and capital structure on liquidity, financial performance, and corporate value. Based on this research, it found that there are significant and negative influences of Sukuk funding, to the corporate value, which leads to the conclusion that especially for investors in Indonesia, has a negative opinion and avoided investing in sukuk issuer, which is most likely due to the investor avoiding Negative impact on the corporate dividend distribution. The results of this research are expected to give a new point of view about sukuk funding in Indonesia especially for academics, investors, and government. Practically, the result of this research show that corporate need to make different action and decition between sukuk bonds and conventional financing.